Utility of the CLIF-C AD score to assess readmission in patients with acute decompensation of non-ACLF cirrhosis. - Cristian A. Oviedo-Garza; Alejandro Peña-Montes; María R. Herrero Maceda; Scherezada M. Loza-Mejia (Annals of Hepatology)
Introduction and Objectives: Patients with cirrhosis who require hospitalization due to acute decompensation (ascites, digestive bleeding, hepatic encephalopathy, among others), have a variable adverse prognosis, depending on whether they have acute-on-chronic liver failure (ACLF), the CLIF-C AD test allows to identify the risk of readmission, development of ACLF and mortality. Materials and Patients: A cross-sectional study was carried out between October 2023 and May 2024. The CLIF-C AD test was calculated in patients with decompensated cirrhosis. The results were analyzed using descriptive statistics, frequency analysis, and percentages. Group comparison analysis was performed with Student's T and chi square as appropriate, to determine the sensitivity and specificity of this test, and a ROC curve was performed; Likewise, Kaplan Meyer curves of 2 groups were used according to the CLIF-C AD categorized as 62 or less and greater than 62; having a significant value of p:0.005; The analysis was performed with the statistical program SPSS version 25. Results: There were 40 patients; 32 men and 8 women. Cirrhosis etiology: alcohol 30 patients (75%), MASLD 8 patients (20%), autoimmune hepatitis 2 patients (5%). Cause of decompensation: Upper digestive bleeding in 19 patients (47.5%), urinary infection in 8 patients (20%), tense ascites in 4 patients (10%), spontaneous bacterial peritonitis in 3 patients (7.5%). Findings on admission: ascites 27 patients (67.5%), hepatic encephalopathy 27 patients (67.5%), shock 18 patients (45%). The CLIF-C-AD score with a median of 68 IQR (52-73). Readmission 35 patients (87.5%); The cause of readmission was hepatic encephalopathy in 17 patients (42.5%), upper digestive bleeding in 10 patients (25%), and acute kidney injury in 3 patients (7.5%). Using Student's T, the CLIF-C AD score is determined for those who were readmitted with a mean of 66 and for those who were not readmitted with a mean of 41 (p<0.001). In the ROC curve, the area under the curve was found to be 0.950 with 95% CI (0.890-1.000) p=0.001, sensitivity 77%, specificity 100%, with a Youden point of 62 points; Therefore, it is categorized into 2 groups based on this score for a cumulative incidence of readmission by Kaplan Meier curve, showing a difference between the groups with a Log Rang test of 0.005. Conclusions: The CLIF-C AD score is a practical, adequate, and useful tool to determine the outcome of decompensated cirrhotic patients, which will allow the identification of high-risk patients and the implementation of close follow-up strategies and timely therapeutic adjustment and avoid adverse outcomes. More studies are required and increased sample size.